(untitled) (Sciences & Technologie. B, Sciences de l’ingénieur, 2015)
Robust control based on fractional order calculus is gaining more and more interests from the control community. In this paper, a robust automatic voltage regulator (AVR) design based on fractional order calculus is presented. The controller design strategy is drawn up such that the open loop transfer function of the AVR system is the Bode’s ideal transfer function that is widely used in the fractional order control domain because of its iso-damping property which is an important robustness feature. The controller design consists of choosing the poles and the zeros of the proposed controller to force the AVR open-loop transfer function to be the Bode’s ideal transfer function. The basic ideas and the derived formulations of the controller design are presented. Simulations were made to test the effectiveness and the usefulness of the proposed controller design approach. Performances analysis to variations of the gain and the time constant of the generator of the AVR were also presented. Comparisons are made with PID controllers to show the robustness efficiency of the proposed design with respect to the generator parameters uncertainties.